Introduction - Ferretti, Francesco; Gensini, Stefano (Theoria et Historia Scientiarum, 2016)
This issue of THS is concluded by W. Skrzypczak’s review of Postcolonial English, an ample book published by E. W. Schneider in 2007. Drawing the reader’s attention to English-based pidginization and creolization processes in several countries, the author casts light on very different cases of linguistic and cultural contacts. Obviously, the book is first of all addressed to scholars (anthropologists, linguists, historians) in the postcolonial field, and most particularly of the English language. However, it deserves attention from researchers of the language origins, too. It was no accident that the case of pidgin and creole languages played so relevant a role in the early elaborations on the concept of “protolanguage”.